On Hormone Action in the Mammary Gland - Rosen, J.M. (Cold Spring Harbor Laboratory Press, 2012)
The importance of systemic reproductive hormones in mammary gland development and breast cancer has been known for more than a century. In fact, the first targeted therapy for cancer was the development of tamoxifen, as an estrogen receptor (ER) antagonist. Based on studies performed primarily in a few breast cancer cell lines, the textbook concept of steroid hormone action at present is that on ligand binding, steroid receptors translocate into the nucleus and stimulate proliferation, and that this effect is mediated by specific coregulators. More recently, as nicely discussed by Brisken and O’Malley (2011), the concepts of specific receptor-positive sensor cells for systemic hormones, and paracrine mediators regulating the development and proliferation of proximal cells has been elegantly shown by the use of genetically engineered mice and chimeric transplantation experiments. One key question raised by these studies is, “How is the patterning of hormone receptor-positive sensor cells established during normal development?” As described by Visvader and Smith (2011), mammary stem cells lack the estrogen and progesterone receptors, and these receptors are first expressed at a still-undefined stage of the mammary cell hierarchy following the appearance of ductal and alveolar progenitors. So how is this process regulated appropriately to provide the correct temporal and spatial expression of the receptor-positive ductal and alveolar cells needed for normal ductal morphogenesis and alveolargenesis? Furthermore, what happens when this process is inappropriately regulated during early breast cancer progression when there may be a switch from paracrine to autocrine signaling mechanisms?